Altered Posterior Cerebellar Lobule Connectivity With Perigenual Anterior Cingulate Cortex in Women With Primary Dysmenorrhea - Wu, Xiaoyan; Yu, Wenjun; Tian, Xuwei; Liang, Zhiying; Su, Yun; Wang, Zhihui; Li, Xiumei; Yang, Li; Shen, Jun (Frontiers in Neurology, 2021)
Objectives: To investigate the potential connectivity mechanism between the cerebellum and anterior cingulate cortex (ACC) and the cerebellar structure in the Primary dysmenorrhea (PDM). Methods: We applied the spatially unbiased infratentorial template of the cerebellum (SUIT) to obtain anatomical details of cerebellar lobules, upon which the functional connectivity (FC) between the cerebellar lobules and ACC subregions were analyzed and the gray matter (GM) volume of cerebellar lobules were measured by using voxel-based morphometry (VBM) in 35 PDM females and 38 age-matched healthy females. The potential relationship between the altered FC or GM volume and clinical information was also evaluated in PDM females. Results: PDM females showed higher connectivity between left perigenual ACC (pACC) and lobule Vermis_VI, left pACC and left lobule IX, right pACC and right cerebellar lobule VIIb, than the healthy controls. Compared with healthy controls, no altered GM volume was found in PDM females. No significant correlation was found between altered cerebellum-ACC FC and the clinical variables in the PDM females. Conclusion: PDM females have abnormal posterior cerebellar connectivity with pACC but no abnormal structural changes. ACC-cerebellar circuit disturbances might be involved in the PDM females.